Divergent Meanings of the «Popular». Sarmiento, Sastre and their allies in the field of primary education of the City of Buenos Aires during the early liberal era (1852-1872) - Caruso, Marcelo; Rodríguez Wehrmeister, Marco (Historia y Memoria de la Educación, 2018)
This article analyses the changing school policies in the city of Buenos Aires between the fall of Juan Manuel de Rosas’ regime and the imposition of a unified curriculum in the city in 1872. Local school policies were erratic and even conflicting in their priorities and were influenced by different social and educational groups. Different strategies and the emergence of educational factions within the school administration are seen as being largely the result of different postures regarding the crucial issue of the meanings of the «popular ». These meanings affected both the political and the educational spheres. In this constellation, a liberal faction led by Sarmiento maintained the strong political meanings associated with the popular, which included a strong confidence in the active participation of civil society in the regulation and improvement of the schools as well as a consistent concern about the extension of school attendance. Another faction was rather Catholic in its liberalism and had in Marcos Sastre, a writer and educationist, its central figure. This faction defended a sceptical perspective about the popular in the field of education and focused on pedagogical issues to the detriment of a more political approach